Pemindahan Ibu Kota Indonesia dan Kekuasaan Presiden dalam Perspektif Konstitusi - Fikri Hadi; Rosa Ristawati (Jurnal Konstitusi, 2020)
In 16 August 2019, the President of Republic of Indonesia gave speech on an idea of the translocation of the Indonesian capital city. The new capital city has also already decided by the President. The decision is made before the legal analysis including the legal basis of the decision to have new capital city. This paper will discuss the concept of the capital city from general- legal perspective to comparative perspective. This paper also discuss on how the concept of capital city is developed in Indonesia from the historical constitutional perspective. It will also analyze the presidential authority on the idea of proposing and deciding the translocation of the capital city. The argument in this paper is written as a legal argument by having perspective on the doctrinal-legal approach. It will use conceptual approach, legal and statutes approach and constitutional history approach. This paper ends up with the conclusion that the concept of the Indonesian capital city is different from the concept of the capital city in other countries, such as the Netherlands and Malaysia. In both countries, the concept of capital city is separated from the concept of government city, which is as the city center for governmental affairs. Besides, it is concluded that based on the Indonesian Constitution, the President of Republic of Indonesia has no absolute authority on the issue of translocation of the capital city. The President of Republic of Indonesia may have the power to propose the translocation of the capital city but there shall be further process of joint discussion and joint approval by the President and the DPR.